PROSODIC PROPERTIES OF CLAUSAL PARENTHETICALS IN SERBIAN (Živi jezici: Journal for Foreign Languages and Literatures, 2023)
The aim of this paper is to present an analysis of the prosodic properties of clausal parentheticals in Serbian in terms of their pitch, intensity, articulation rate and prosodic domain in relation the surrounding anchor clauses. Regarding the pitch and intensity, the results indicate that the utterance seems to follow a downward trend regardless of the parenthetical interpolation. Considering the rate of articulation, no pattern can be established in the behavior of clausal parentheticals in relation to their anchor clauses. When it comes to the intonational domain, the clausal parentheticals in Serbian tend to form separate intonational phrases, thus belonging to the group of ‘prototypical parenthesis’, in Dehé’s (2014) terms.